Developing implementation science to improve the translation of research to address low back pain: A critical review. Issue 6 (December 2016) - Hodder, Rebecca Kate; Wolfenden, Luke; Kamper, Steven J.; Lee, Hopin; Williams, Amanda; O'Brien, Kate M.; Williams, Christopher M.
Abstract: The evidence base regarding treatment for back pain does not align with clinical practice. Currently there is relatively little evidence to guide health decision-makers on how to improve the use, uptake or adoption of evidence-based recommended practice for low back pain. Improving the design, conduct and reporting of strategies to improve the implementation of back pain care will help address this important evidence-practice gap. In this paper, we 1) Describe implementation science models and approaches. 2) Outline important features of implementation research. 3) Critically appraise the quality and findings of implementation trials in the low back pain field. 4) Provide recommendations for the design and conduct of future implementation studies in the field.